Pengaruh Pemberian Pupuk Kandang Kambing dan Pupuk NPK terhadap Pertumbuhan dan Hasil Tanaman Kubis Bunga (Brassica oleraceae Var. Botrytis L.) - Prayogi, Aang Dwi; Safitri, Betari; Rahhutami, Ratih; Febria, Dila (Politeknik Negeri Lampung, 2025)
This study aimed to determine the effect of goat manure and NPK fertilizer on the growth and yield of cauliflower (Brassica oleracea var. Botrytis L.) of the Larisa F1 variety. The research was conducted from November 2024 to January 2025 using a factorial Randomized Block Design (RBD) consisting of two factors: goat manure doses (10, 20, and 30 tons ha⁻¹) and NPK fertilizer doses (200, 400, and 600 kg ha⁻¹), resulting in nine treatment combinations with three replications. Observed variables included plant height, number of leaves, curd diameter, curd weight, fresh weight, and dry weight of plants. The results showed that both goat manure and NPK fertilizer significantly influenced several growth and yield parameters, including early-stage plant height, number of leaves, curd diameter, fresh weight, and dry weight. Goat manure at doses of 20–30 tons ha⁻¹ produced better growth and yield compared to the lowest dose, while increasing NPK fertilizer to medium and high levels contributed positively to vegetative development and biomass accumulation. No interaction between the two factors was observed.